2003
DOI: 10.1002/bip.10551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of possible kinetically significant anion‐binding sites in human serum transferrin using molecular modeling strategies

Abstract: Certain anions have been shown experimentally to influence the rate of iron release from human serum transferrin (HST), implying the existence of one or more allosteric kinetically significant anion-binding (KISAB) sites on or near the surface of the protein. A rank-ordered selection of potential HST KISAB sites has been obtained using a novel three-stage molecular modeling strategy. The crystal structure of HST (1A8E.pdb) was first subjected to a heuristic analysis, in which positively charged and hydrogen-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 140 publications
(176 reference statements)
0
11
1
Order By: Relevance
“…We suggest that the absence of Lys144 might increase access of chloride ions to Arg143, resulting in an enhancement of iron release relative to the control. Although both Arg143 and Lys144 were suggested as a potential KISAB sites in a modeling study (42), our data clearly show that, unlike Arg143, Lys144 does not meet the criteria for this designation.…”
Section: Discussioncontrasting
confidence: 68%
“…We suggest that the absence of Lys144 might increase access of chloride ions to Arg143, resulting in an enhancement of iron release relative to the control. Although both Arg143 and Lys144 were suggested as a potential KISAB sites in a modeling study (42), our data clearly show that, unlike Arg143, Lys144 does not meet the criteria for this designation.…”
Section: Discussioncontrasting
confidence: 68%
“…To check whether our CSCs overlapped with allosteric couplings, and to which extent, we explored the literature and the Allosteric Database[ 72 ] (ASD, version 2.0). The information retrieved shows that experimental data were available for nine proteins: aldolase[ 73 , 74 ], annexin V[ 75 78 ], transferrin[ 79 82 ], retinol-binding protein[ 83 86 ] (RBP), purine nucleoside phosphorylase[ 87 , 88 ] (PNP), heat shock protein HSP90[ 89 ], cyclophilin A[ 90 92 ], interleukin-1alpha[ 93 , 94 ], and Awd nucleotide diphosphate kinase[ 95 ]. When comparing functional site (FS)/allosteric site (AS) annotations with our CSC data, we found several cases where the regions linked by both couplings overlapped: one cavity in the CSC would involve a number of FS residues and the other cavity would involve a number of AS residues (see below).…”
Section: Methodsmentioning
confidence: 99%
“…This high anion-binding affinity is consistent with the hypothesis that these anionic ligands can increase the value of k max by binding to an allosteric anion-binding site in the protein. Computational studies have identified a number of potential anion-binding sites in the Nlobe of ferric-transferrin [46]. However, it must be stressed that the binding constants in Table 4 are for apotransferrin, not ferric transferrin.…”
Section: Mechanism Of Iron Releasementioning
confidence: 97%